Assessment of Dental Caries and Intervention in the First Permanent Molars of Brazilian Children - Juliana Campos Chaves; Tatiane Ramos dos Santos; Mirian de Waele Souchois de Marsillac; Adilis Alexandria; Tatiana Kelly da Silva Fidalgo (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2021)
Objective: To evaluate the prevalence of caries stages and interventions on first permanent molars (FPM) in Brazilian children. Material and Methods: Data from FPM were extracted from dental records of children aged 5-14 years of age that attended the UERJ Pediatric Dentistry Clinic. Data include patient age, sex, biofilm index, presence of carious lesions in all stages, and the treatments. Data was analyzed using the SPSS® 20.0 program. Results: A total of 158 dental records were analyzed, 587 registers were related to the caries stage and 601 related to the interventions; mean age of 8.26 (±1.4 years) and 53.2% were girls. The prevalence of active/inactive white spot (AWS/IWS) varied from 14.3% to 21.6% in right upper and lower left FPM, respectively. Enamel/dentin lesions without pulp involvement were also more prevalent in the lower arch and ranged from 3.4% for the right upper to 11.5% for the lower right FPM. Cavities with pulp involvement or indicated extraction ranged from 0% to 1.4%. Treatment included dental sealants, varying from 17.1 to 24.0% (n=126) and restorations, varying from 1.3 to 11.8% (n=38). The lower right were the most affected teeth. Conclusion: First permanent molars presented a higher prevalence of dental caries in early stages and the most prevalent treatment was related to the initial carious process, fluor therapy and sealants.